The effects of prey, habitat heterogeneity and fire on the spatial ecology of peninsular Diamond Pythons (Morelia spilota spilota: Pythonidae). (6th May 2013) - Michael, Damian R.; Cunningham, Ross B.; Macgregor, Christopher; Brown, Darren; Lindenmayer, David B.
Abstract Understanding an organism's home range is an important component of effective wildlife management. However, home ranges can vary spatially and temporally within and between populations. Landscape ecology theory can provide a framework for understanding spatio‐temporal variability in animal traits. We used radio‐telemetry in a population of diamond python Morelia spilota spilota Lacépède (Pythonidae) from a biologically rich and structurally heterogeneous reserve in eastern Australia to explore the relationship between home range size, optimal foraging theory and vegetation mosaic theory. Twelve adult snakes were tracked between September 2004 and February 2008. Male home ranges were significantly larger (P < 0.05) and more variable (41 ± 30 ha) than female home ranges (23 ± 5 ha), and males moved further between observations (123 m c.f. 65 m). Core activity centres varied significantly among habitat (P < 0.05) with larger home ranges observed in heathland, a vegetation community which supported comparatively low mammal diversity. No other variables examined including number of fixes, body length, prey abundance, vegetation heterogeneity or fire history explained home range variability. In this system, relatively high mammalian prey diversity and rapid post‐fire vegetation succession may limit prey availability and fire effects as being significant determinants of home range variability in M. spilota.